Deiksis dalam Cerpen “Senyum Karyamin” Karya Ahmad Tohari Sebagai Materi Pembelajaran dalam Bahasa Indonesia - Chelfia Luthfi Intan Pratiwi; Asep Purwo Yudi Utomo (Lingua Susastra, 2021)
The problem of deixis is an obstacle in understanding reading texts, especially literary works. This study aims to identify and describe deixis in short story literary works. In addition, the findings of this study aim to be a medium in Indonesian language learning activities, especially in text description material. This research is a qualitative research with descriptive method. The data collection method is observational note-taking. The technique of analyzing the data used in this study is to use the data analysis technique of the Miles and Huberman model. Based on the research findings, there are five types of deixis in the Senyum Karyamin short story, namely person, place, time, discourse, and social. Through the identification of this deixis, learning to understand descriptive text will be easier to implement.